Enhancement of a Power System Transient Stability Using Static Synchronous Compensator STATCOM - Naseer M. Yasin; Mustafa M. Al-Eedany (Engineering and Technology Journal, 2013)
In modern power system utilities, increased power demand often lead to the situation where the system no longer remains in secure operating region. Flexible AC Transmission Systems (FACTS) controllers can play an important roll in power system security enhancement. The goal of FACTS devices study is to measure their impact on the state of the electrical networks into which they are introduced. Their principal function is to improve the static and dynamic properties of the electrical networks and that by increasing the margins of static and dynamic stability. In this paper the modeling of Static Synchronous Compensator (STATCOM) within Newton-Raphson power flow equations has been presented, discussed, implemented and the transient stability of a power system was tested when three phase fault is applied at a certain branch of the power system. Case studies are carried out on a 5- bus and a 30-bus test systems to demonstrate the effectiveness of the proposed model.